The academic response to COVID-19 - Rijs, Chantelle; Fenter, Frederick (Frontiers in Public Health, 2020)
COVID-19 has posed an unprecedented challenge to the international scientific community. Along with the disruption faced by most of the world’s population, many researchers have felt an added pressure to understand, cure and mitigate the virus. In order to capture the initial impact of the coronavirus pandemic on the international scientific community, this survey with our authors, editors and reviewers was run in May and June 2020. In one of the largest academic surveys ever conducted, 25,307 members of our academic community participated, representing diverse countries, roles, and areas of research.